Analysis of Occupational Safety in the Flour Production Process Application of Occupational Safety and Health Using the HIRADC Method in the HIRARC Flour Production Process - Gunawan, Taopik Sendy; Sena, Boni (Journal of Education Technology Information Social Sciences and Health, 2024)
Occupational Safety and Health (K3) is a critical aspect in the rice production industry, which is often ignored, due to non-compliance with K3 standards, various problems have been identified. Meanwhile, the HIRADC (Hazard Identification, Risk Assessment, and Determining Controls) method is an important tool in occupational safety and health management that is used to identify hazards, assess risks, and determine appropriate control measures. This research aims to provide a brief explanation regarding the application of the HIRADC method in industrial work environments. The HIRADC process includes three main stages: hazard identification, risk assessment, and control determination. Hazard identification is carried out to identify potential causes of injury or loss. A risk assessment assesses the frequency and impact of each identified hazard, while a control determination focuses on implementing measures to eliminate or reduce the risk. The research results show that the systematic application of the HIRADC method can improve work safety and reduce the incidence of work-related accidents and illnesses. In conclusion, HIRADC is an effective method that can be integrated in a safety management system to create a safer work environment. This research aims to identify hazards, assess risks, and determine control measures in the flour production process using the HIRADC (Hazard Identification, Risk Assessment, and Determining Controls) method. This method is applied at several stages of flour production in industry, from milling to packaging. In this research, the method of direct observation was used during the testing process. The research results show that some of the main hazards identified include exposure to flour dust which can cause respiratory problems, the risk of fire and explosion due to flammable dust, and physical injury from grinding machines. The risk assessment indicates that these risks have a high probability and serious impact on worker health and safety. As control measures, it is recommended to use an effective ventilation system, implement safe machine operating procedures, and provide personal protective equipment (PPE) such as masks and ear protectors. Systematic implementation of the HIRADC method has been proven to increase work safety and reduce accident incidents in flour mills. In conclusion, HIRADC is an effective tool in managing occupational safety and health risks in the flour production industry.